Suicide by Sharp and Stab Instruments Two Case Reports - Erkol, Zerrin; Büken, Bora; Yılmaz, Rıza; Erkol, Hayri (The Bulletin of Legal Medicine, 2007)
SUMMARY In this paper, two suicidal case, due to sharp and stab wounds, were presented. First case was 68-year-old man, died a deeply incision on the internal elbow region, which was reaching to bone and cutting arterial, venous, nervous and muscular structure totally by using bread knive’s sharp edge and dead due to external bleeding from vessels of brachialis. Second case was 23-year-old woman, died four stab wounds on the superior umbilical region, one was reaching through the abdominal cavity and cutting inferior vena cava, whereas the other ones were superficial. Death was due to internal bleeding from cutting of inferior vena cava in this case. Because these suicidal methods are not seen frequently in the lethal suicidal case, this case reports presented and findings were discussed according to literature in this subject. Key words: Suicide, sharp wounds, stab wounds, origin